Osmotic dehydration combined with air drying of red pitaya fruit cubes. - Najafi, Assal Haj (2010)
The main objectives of this study are to investigate the effects of different temperatures on osmotic dehydration of red cubical pitaya fruit and subsequently physical quality evaluations, in developing dried pitaya cubes as a new healthy snack product. Two major steps were involved (i) an osmotic dehydration process was used as a pre-treatment and (ii) an air drying process in a cabinet dryer was used for further drying. The effect of sugar solution concentration (40, 50 and 60%), temperature (25, 30 and 35 ˚C) and air velocity (1 and 3 ms־¹) and also air temperature for the air drying process (40, 50 and 60 ˚C) were studied. Sampling was performed every 15 minutes for 2 hours, then at 4, 6, 24, 48 and 72 hours of immersion. Then pitaya slices were removed from the solution in order to investigate dehydration efficiency and equilibrium stage of dehydration. Osmotic dehydration kinetics was modelled according to Peleg, and Page equations. Both models were evaluated using two statistical measures, correlation coefficient, and root means square error. The statistical parameters (R² and RMSE) indicated that both models can predict good fitting with moisture content, weight reduction, and sugar gain and water loss. But the best fitting for weight reduction and sugar gain were obtained using Peleg equation. The Page empirical model presented a good fit of the water loss experimental data. Addition of sucrose to osmotic solutions decreased the driving force of the process and resulted in higher water loss and sugar gain. Colour saturation values increased, denoting colour intensification during the process of osmotic dehydration. Lightness of the pitaya cubes decreased as the sugar concentration increased. The greatest changes in Total Colour Difference of osmotic dehydrated samples occurred in 50 and 60% sugar solutions. An increase of concentration and passing time cause softer texture in product compared to the fresh pitaya. However, based on the air drying process, the best osmotic dehydration condition was a sugar concentration of 60% at 35 ˚C with a contact time of 2 hours. This treatment could remove more water of the samples, therefore air drying time reduced. Pitaya samples were air dried in a cabinet dryer at 40, 50 and 60 ˚C with two different air velocities of 1 and 3 ms־¹ for 8 hours. Among the pre-treatment conditions, the sucrose concentration, temperature and immersion time significantly (p < 0.05) influenced the air drying time. Osmotic dehydrated pitayas that were air dried at 60 ˚C showed a large moisture decline in the early drying periods similar with the drying rates of untreated samples. At the beginning of the drying process of fresh pitaya, drying rate was influenced by air temperature. Air dried samples at 40 ˚C showed lower drying rates attributed to sugars concentration on the outer layers of pitaya tissue and their crystallization during drying, but had better colour retention during drying. In the air dried osmotic dehydrated samples at 60 ˚C a greater texture hardening was observed. The best product was obtained in the following operational condition: air temperature of 60 ˚C, air velocity of 1 and 3 ms־¹ and contact time of around 5 hours (with 22.78% to 22.3% moisture content) for air drying. Because of the short time of drying these conditions help to improve colour and texture of the osmotic dehydrated pitaya cubes. This study provides an extensive understanding of osmotic dehydration of red cubical pitaya at lower temperatures. The results indicate that the process is feasible and may represent a new product for pitaya fruit